2016
DOI: 10.1186/s13046-016-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

High expression of long non-coding RNA SBF2-AS1 promotes proliferation in non-small cell lung cancer

Abstract: BackgroundRecent evidence has proven that long noncoding RNAs (lncRNAs) play important roles in cancer biology, while few lncRNAs have been characterized in NSCLC. Here, we characterized a novel lncRNA, SBF2 antisense RNA 1 (SBF2-AS1), in non-small cell lung cancer (NSCLC).MethodsQuantitative real-time PCR was used to quantify SBF2-AS1 expression in NSCLC tissues and cell lines. The correlation of SBF2-AS1 expression with clinicopathologic features was analyzed in a cohort NSCLC patient. Loss of function and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 35 publications
3
67
1
Order By: Relevance
“…Nuclear and cytoplasmic fraction data also demonstrated that SBF2-AS1 was distributed in the nucleus and cytoplasm, which indicates that SBF2-AS1 may serve multiple functions at the transcriptional and post-transcriptional levels. According to our previous study (19), SBF2-AS1 may also transcriptionally downregulate the expression of CDKN1A via SUZ12 binding within the nucleus, as confirmed by the present study. CDKN1A, a cyclin-dependent kinase inhibitor, serves an important role in cell cycle arrest, and is therefore regarded as a tumor suppressor gene (40).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Nuclear and cytoplasmic fraction data also demonstrated that SBF2-AS1 was distributed in the nucleus and cytoplasm, which indicates that SBF2-AS1 may serve multiple functions at the transcriptional and post-transcriptional levels. According to our previous study (19), SBF2-AS1 may also transcriptionally downregulate the expression of CDKN1A via SUZ12 binding within the nucleus, as confirmed by the present study. CDKN1A, a cyclin-dependent kinase inhibitor, serves an important role in cell cycle arrest, and is therefore regarded as a tumor suppressor gene (40).…”
Section: Discussionsupporting
confidence: 71%
“…Evidence indicates that SBF2-AS1 may function as an oncogenic gene in ESCC. In previous studies, it was reported that SBF2-AS2 was able to bind to suppressor of zeste 12 homolog (SUZ12), a core component of PRC2 (19,(37)(38)(39). The enrichment of SUZ12 subsequently induces the inhibition of trimethylation of histone 3 Lys 27 in the promoter region of CDKN1A, and therefore downregulates the expression of CDKN1A (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the lncRNA ANRIL has been found to be significantly upregulated in NSCLC tissues, and its expression promotes cell proliferation and inhibits cell apoptosis in vitro and in vivo [22] . Moreover, HOTAIR, MALAT1 and SBF2-AS1 have been shown to exert oncogenic functions in NSCLC [23][24][25] . However, even in light of these discoveries, other NSCLC-related lncRNAs and their modulatory effects have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%